Sosialisasi Penggunaan Benih Bawang Putih Varietas Sangga Sembalun dan Pendampingan Pembibitan di Alahan Panjang - Nilla Kristina; Yusniwati Yusniwati; Netti Herawati; Lily Syukriani; Elara Resigia (Yayasan Literasi Sains Indonesia, 2023)
Garlic is a horticultural commodity that has high economic value. However, the development of garlic in West Sumatra is still limited due to the difficulty in obtaining quality seeds. Quality seeds can determine production, productivity levels and quality of production. Quality seed is also the key to seed acceptance by farmers. The purpose of community service is to introduce quality seeds to farmer groups in Nagari Sungai Nanam, Solok Regency. Sangga Sembalun seed is one of the short-lived national superior varieties. These seeds are suitable for planting in the agro-climatic conditions of Nagari Sungai Nanam, Solok Regency. Through this community service activity, it is hoped that the seeds can be reused as a source of seeds by farmers. The results obtained from these service activities are farmers giving a positive response to these service activities. Sangga Sembalun variety is accepted as seed to be developed by farmers. The farmer group also planted Sangga Sembalun seeds to be used as a source of seeds by group members for the next planting.